APLIKASI AUTOCAD DALAM PEMBUATAN PECAH POLA BUSANA WANITA - Nurul Aini (Teknologi dan Kejuruan, 2012)
Abstract: A pattern in clothes making is a mould of one’s shape body , which is made from a paper that is used to making clothes. Based on this pattern, one’s clothes can be made. Basically, there are two stepsin clothes making. The first step is making a basic pattern.  The second step is making a breakdown pattern based on the desired model. The basic pattern and the breakdown pattern is used to be made by hand. By the technology development, these pattern can be made by using computer programme, such as AutoCad.  The use of AutoCAD in clothes pattern making, particularly in producing the breakdown pattern, has not been previously applied. This research sets out to produce basic pattern and pattern breakdown of female clothing patterns by using the AutoCAD. The pattern is made by using the polar angle formula; @distance